Leg length discrepancy after total hip arthroplasty: a review of literature - Desai, Aravind S. (Springer US, 2013)
Discrepancy of leg length is often considered to be a problem after total hip replacement and can adversely affect an otherwise excellent outcome. Furthermore, it has been associated with patient dissatisfaction and remains one of the most common reasons for litigation against the orthopedic community. As a consequence of the need to equalize leg length, several authors have sought to validate methods of minimizing limb length discrepancy based on preoperative planning with preoperative radiological templates or intraoperative methods of measurement. In this article, we present a review of the limb length discrepancy in total hip arthroplasty, its implications and several techniques to avoid it. We recommend that a combination of the above mentioned methods will give the best chance for the surgeon to minimise the risk of leg length discrepancy following total hip replacement.